A Physical Asset Management Strategy Execution Enforcement Mechanism for the early detection and management of Physical Asset Management Strategy Execution Failure - Stimie, Johann (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.